Chemical composition and larvicidal activity of essential oil from leaves of Eucalyptus robusta - Nguyen Thi, Hong Van; Tran , Thi Tuyen; Pham , Cao Bach; Dang, Thu Quynh; Dinh Thi, Thu Thuy; Vo, Thanh Thuong; Ngo, Gia Huy; Nguyen, Quoc Thong; Nguyen, Huy Hung; Do, Huu Nghi (Academia Journal of Biology, 2024)
Essential oil (EO) from leaves of Eucalyptus robusta was extracted by hydrodistillation, and analyzed the chemical composition using gas chromatography- Flame ionization detector (GC-FID), and gas chromatography/mass spectrometry (GC/MS). Thirty constituents from leaf EO were identified accounting for 97.48% of the total composition of EO. Monoterpene hydrocarbons were the major chemical classes (83.34%) in which 1,8-cineole (29.23%), α-pinene (18.58%), α-phellandrene (14.05%) and β-pinene (6.40%) were the main components. The larvicidal activity test against Culex quinquefasciatus showed that the essential oil from the leaves of E. robusta strongly inhibited this southern house mosquito with LC50 values at 24 h and 48h to be 30.34 µg/mL and 28.77 µg/mL, respectively.